The prevalence and pregnancy outcomes of intrahepatic cholestasis of pregnancy: A retrospective clinical audit review. (September 2019) - Gardiner, Fergus W; McCuaig, Ruth; Arthur, Chris; Carins, Thomas; Morton, Adam; Laurie, Josephine; Neeman, Teresa; Lim, Boon; Peek, Michael J
Background: To determine the prevalence and outcomes of intrahepatic cholestasis of pregnancy. Methods: A review comparing intrahepatic cholestasis of pregnancy pregnancies to all other pregnancies in three tertiary care Australian hospitals over a 36-month period. Results: There were 43, 876 pregnancies. The prevalence of intrahepatic cholestasis of pregnancies ( n  = 319) was 0.7%. There were differences between intrahepatic cholestasis of pregnancy and non-intrahepatic cholestasis of pregnancy mothers including higher prevalence of South Asian (22.6% versus 3.1%, p < 0.001), Indigenous Australian (3.8% versus 1.8%, p < 0.05), and Asian ethnicity (8.4% versus 5.7%, p < 0.05), mothers with a body mass index >35 kg/m 2 (10.6% versus 5.5%, p < 0.001), those with diabetes mellitus (25.7% versus 9.8%, p < 0.001), and those with twin births (8.7% versus 2.2%, p < 0.001). The primary clinical outcomes of intrahepatic cholestasis of pregnancy included a median gestational age at delivery of 36.4 (SE 0.09) weeks compared to 38.6 (SE 0.01) weeks (p < 0.001), a lower birth weight (3.12 (SE 0.03) versus 3.31 kg (SE 0.03), p < 0.001), and an increase in special care nursery admissions (44.5% versus 15.3%, p < 0.001). Conclusion: Treated intrahepatic cholestasis of pregnancy in the population described here had similar mortality outcomes although increased special care nursery admission as compared to the general population.